From sole crops to strip cropping: Decision rules of frontrunner farmers in The Netherlands - Stella D. Juventia; Dirk F. van Apeldoorn; Hilde Faber; Walter A. H. Rossing (PLoS ONE, 2025)
Strip cropping, where several crops are grown in adjacent long and narrow multi-row strips, is an innovation niche that challenges monocropping by offering a greater range of ecosystem services, including higher biodiversity and aesthetic value at similar yield. It can be implemented within the current regime by adjusting the strip width to fit machinery working width. However, its novelty and complexity, that mobilize four dimensions of diversity—space, time, gene, and operational crop management—make transitions from monocropping difficult. This study aims to learn from the experiences of strip cropping frontrunners by: 1) capturing the contexts, objectives, challenges, and outcomes of farmers’ first-year strip cropping experience, and 2) identifying patterns in farmers’ decision rules following its uptake. Semi-structured in-depth interviews were conducted with ten Dutch farmers with at least one-year strip cropping experience. Upon formulating the farmers’ operational management decision rules, we used two analytical lenses to find patterns in the changes compared to monocropping. Results showed that all farmers shared the objective of increasing insect biodiversity. Common challenges included a lack of agro-ecological knowledge and experience, incompatible machinery working width, and crop neighbor damage. Most farmers positively evaluated the feasibility to adjust or acquire adapted machines, were neutral on yield changes, and negatively evaluated workload. We identified 49 decision rules comprising 113 condition-decision relations. We found two clusters or archetypes of farmers that differed in their propensity to adjust mechanization. No pattern was found among the other adjustments from monocropping to strip cropping, indicating that changes were highly farmer-specific. The two most often mentioned decisions included machine investment and crop choice adjustment. These apparent key decisions may guide exchanges among strip cropping farmers, advisors, and researchers. Leveraging diverse decision rules captured in this study, alongside strengthening the infrastructure and institutional support for strip cropping will help farmers transition towards sustainable agricultural systems.